2013
DOI: 10.1364/boe.4.000481
|View full text |Cite
|
Sign up to set email alerts
|

Sensitive and specific discrimination of pathogenic and nonpathogenic Escherichia coli using Raman spectroscopy—a comparison of two multivariate analysis techniques

Abstract: The determination of bacterial identity at the strain level is still a complex and time-consuming endeavor. In this study, visible wavelength spontaneous Raman spectroscopy has been used for the discrimination of four closely related Escherichia coli strains: pathogenic enterohemorrhagic E. coli O157:H7 and non-pathogenic E. coli C, E. coli Hfr K-12, and E. coli HF4714. Raman spectra from 600 to 2000 cm−1 were analyzed with two multivariate chemometric techniques, principal component-discriminant function anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
36
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(39 citation statements)
references
References 31 publications
(30 reference statements)
2
36
0
Order By: Relevance
“…T echnologies developed for the detection and identification of microorganisms, particularly bacteria, are of great concern in many areas of research, especially in the search for signs of life on the inner planets of the Solar System (Gilbert et al, 2009;Davis et al, 2012;Hamasha et al, 2013). A fundamental issue with the discovery of signs of life in the context of space exploration missions is that potential habitable planets can be contaminated by Earth life signatures (forward contamination), which in turn can be falsely registered as alien life (Crawford, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…T echnologies developed for the detection and identification of microorganisms, particularly bacteria, are of great concern in many areas of research, especially in the search for signs of life on the inner planets of the Solar System (Gilbert et al, 2009;Davis et al, 2012;Hamasha et al, 2013). A fundamental issue with the discovery of signs of life in the context of space exploration missions is that potential habitable planets can be contaminated by Earth life signatures (forward contamination), which in turn can be falsely registered as alien life (Crawford, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have reported that Raman spectroscopy is useful for microbe identification. Hamasha et al [15] reported that Raman spectroscopy coupled with multivariate statistical techniques showed N95% sensitivity and specificity for identifying four different E. coli strains. In particular, the performance of E. coli strain identification through Raman spectroscopy was improved by combining the laboratory approach with two multivariate chemometric techniques, PC-discriminant function analysis and partial least squaresdiscriminant analysis.…”
Section: Multivariate Statistics-assisted Classificationmentioning
confidence: 99%
“…Recent reports have suggested that Raman spectroscopy is useful for rapidly detecting and classifying microbes [11,[13][14][15][16]. Raman spectroscopy is a label-free optical sensing technology based on the inelastic scattering of light by molecules.…”
Section: Introductionmentioning
confidence: 99%
“…In the area of pathogen detection and identification, several studies have been reported in the last few years [22][23][24][25][26][27][28] . However, there is not a single method available so far to Defence Life Science Journal, Vol.…”
Section: Introductionmentioning
confidence: 99%